Effect of Annealing Atmosphere on the Recrystallized Texture and Abnormal Grain Growth of Ni–5%W Alloy Sheets1. Issue 11 (7th April 2015) - Ateba Betanda, Yanick; Helbert, Anne‐Laure; Brisset, François; Waeckerlé, Thierry; Baudin, Thierry
Abstract : The effect of the annealing atmosphere on the recrystallization of Ni–5%W alloy used as substrate sheet for superconductor wire was investigated. The annealing was made in two different annealing atmospheres: hydrogen and argon. After analyzing the recrystallized texture and microstructure by EBSD, the main texture component formed in both annealing atmospheres is the 100<001> cube orientation. Furthermore, it is shown that hydrogen promotes the cube texture development, while argon slows down its development. Besides, it is shown that hydrogen favors the triggering of the abnormal grain growth at a temperature higher than 1 120 °C, while under argon, the abnormal grain growth is not observed before 1 200 °C. Then, an optimized annealing process has been put forward combining both the atmospheres. Note that the origin of hydrogen and argon effects on boundary mobility is also discussed. Abstract : The effect of two annealing atmospheres (hydrogen and argon) on recrystallized texture and abnormal grain growth (AGG) of Ni5%W alloys sheets are compared. It is shown that hydrogen promotes the cube texture development, while argon slows it down. Hydrogen is shown to favor the triggering of AGG at a temperature higher than 1 120 °C, while under argon, abnormal grain growth is not observed before 1 200 °C. An optimized annealing process is proposed, combining both atmospheres in order to increase the fraction of cube orientation without triggering AGG.